The functional of cathepsin L in the ontogenesis and reproductive regulation of the Asian corn borer, Ostrinia furnacalis - Jin-Shan Zhang; Jin Li; Jian-Yu Meng; Xue Tang; Hajra Saddique; Chang-Yu Zhang (Scientific Reports)
Abstract The Asian corn borer, Ostrinia furnacalis, seriously cause damages to the quality and yield of corn and has developed a high level of resistance against synthetic chemicals currently used against this pest. Therefore, there is an urgent need to find a novel control method for O. furnacalis. Cathepsin L (CTSL) plays various roles in insects, including growth and development, metamorphosis, tissue dissociation, and embryonic development. However, to date, OfCTSL has not been characterized in O. furnacalis. Our results showed that the 1,653 bp cloned length of OfCTSL contains an open reading frame (ORF) of 1,026 nucleotides (nt), which encodes 341 amino acids (aa). The OfCTSL includes two conserved domains such as the cathepsin propeptide inhibitor domain (I29) and cysteine protease Pept_C1 domain. Phylogenetic and homology analyses showed that OfCTSL is highly conserved in among Lepidopteran insects. RT-qPCR analysis showed that OfCTSL was highly expressed in the pupal stage and hemolymph of the 5th instar larvae of O. furnacalis. Knockdown of OfCTSL by nanocarrier-mediated RNA interference significantly inhibited larval molting, pupation, and reduced the egg-laying capacity. These findings demonstrate that OfCTSL plays a vital role in the ontogenesis and reproduction of O. furnacalis, making it a potential target for controlling this destructive pest.